ESPERANZA DE VIDA EN VEINTE ESTADOS DE LA REPUBLICA MEXICANA (I) - BUSTAMANTE, MIGUEL E; ALDAMA C, ALVARO (ACADEMIA NACIONAL DE MEDICINA, 1949)
Data are given in abridged form on life expectancy in 20 Mexican States, representing a sample of all geographic, climatic and economic sections of the nation, and containing 75% of the total population of the nation In Yucatan and Coahuila life expecta
REV INST SALUBR ENFERM TROP
Keywords: ESPERANZA, VIDA, ESTADOS, MEXICANA; CIENCIAS MEDICAS; SALUD PUBLICA; ESPERANZA DE VIDA